Education System of Modern Islamic Boarding School in The Postmodern Era - Kamaluddin MH Pasi; Rasyidin Rasyidin; Radinal Mukhtar Harahap (Nazhruna: Jurnal Pendidikan Islam, 2020)
This article aims to explore information about Islamic Boarding School (Pesantren) incredibly Modern related to Postmodernism. The traditionalism of Pesantren in the early days is considered to have changed with modernism. The answer to the influence of Postmodernism to be found by the method of description-comparison-interpretation of the data obtained. The discussion shows that the effect of the movement of thought is only the lexical meaning of renewal. As for Pesantren's principles, characteristics, or fundamental values remains valid and become an institution that becomes a tradition in the body of Islamic Education thinking. It can also be said that the better (al-ashlah) taken by him and keeping the good (al-shâlih), means is his traditions. A tradition that is considered similar to other thought movements is Pesantren's dynamic attitude. Similarly, Waqf is the basis of ownership in Pesantren which replaces the Foundation system. It is not a new item, so its value remains in the Islamic tradition. Thus it can be understood that Pesantren continues to return to the rule of existing Islamic educational institutions, which aims to give the life of the world and the hereafter to everyone related to it.